2022
DOI: 10.5194/gmd-15-1545-2022
|View full text |Cite
|
Sign up to set email alerts
|

A parameterization of long-continuing-current (LCC) lightning in the lightning submodel LNOX (version 3.0) of the Modular Earth Submodel System (MESSy, version 2.54)

Abstract: Abstract. Lightning flashes can produce a discharge in which a continuing electrical current flows for more than 40 ms. Such flashes are proposed to be the main precursors of lightning-ignited wildfires and also to trigger sprite discharges in the mesosphere. However, lightning parameterizations implemented in global atmospheric models do not include information about the continuing electrical current of flashes. The continuing current of lightning flashes cannot be detected by conventional lightning location … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The details of the sensor and the reported climatology of lightning and LCC lightning between 1998 and 2014 can be found in [46][47][48][49][50][51]. We used the method globally developed by [51] and recently employed by Pérez-Invernón et al (2021) [20] (over the Mediterranean Basin) and Pérez-Invernón et al (2022) [21] (globally) to classify lightning flashes reported by TRMM-LIS according to the duration of the continuing phase. The duration of the continuing phase detected by TRMM-LIS should be considered a minimum.…”
Section: Lightning Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the sensor and the reported climatology of lightning and LCC lightning between 1998 and 2014 can be found in [46][47][48][49][50][51]. We used the method globally developed by [51] and recently employed by Pérez-Invernón et al (2021) [20] (over the Mediterranean Basin) and Pérez-Invernón et al (2022) [21] (globally) to classify lightning flashes reported by TRMM-LIS according to the duration of the continuing phase. The duration of the continuing phase detected by TRMM-LIS should be considered a minimum.…”
Section: Lightning Datamentioning
confidence: 99%
“…The ignition phase is supposed to be influenced by the characteristics of the lightning discharge and the vegetation. Long-Continuing-Current (LCC) lightning with a duration between 40 ms and 282 ms have been proposed as the main precursors of LIW [18][19][20][21]. LCC lightning flashes transport a significant amount of electrical charge between the cloud and the attachment point.…”
Section: Introductionmentioning
confidence: 99%
“…The LNOX submodel of MESSy estimates the total lightning flash density, the LCC lightning flash density, and the production of NO x by lightning by using different lightning parameterizations [15] and a scaling factor that ensures a global lightning occurrence rate of ∼45 flashes per second [46,60]. For the present study, we use the lightning parameterization based on the Cloud Top Height (CTH) [24] for land and on the convective precipitation [61] for ocean as proposed by Pérez-Invernón et al (2022) [25] and scaled by a factor of 1.13. This lightning parameterization overestimates the lightning flash density over the ocean with respect to land, producing a land/ocean contrast of about 1 : 1 instead of the 3 : 1 contrast reported by space-based instruments [46,47,60].…”
Section: Lightning Parameterizationmentioning
confidence: 99%
“…1b), suggesting that a variation in lightning frequency does not necessarily imply the same varia- The criterion to consider the MUMF in the calculation of the annual average is that the cloud thickness is at least 3 km and that the lightning occurrence rate is larger than 1.433× 10 −14 m −2 s −1 ) [15]. The MUMF have been multiplied by 6.57 as it is applied in the parameterization of LCC lightning [25]. Changes are calculated as the difference between RCP6.0 and present-day simulations.…”
Section: Lightning Projectionsmentioning
confidence: 99%
See 1 more Smart Citation